2007
DOI: 10.1086/511295
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Mid‐UV Spectroscopic Indices of Stars

Abstract: Using the UVBLUE library of synthetic stellar spectra we have computed a set of mid-UV line and continuum spectroscopic indices. We explore their behavior in terms of the leading stellar parameters (T eff , log g). The overall result is that synthetic indices follow the general trends depicted by those computed from empirical databases. Separately we also examine the index sensitivity to changes in chemical composition, an analysis only feasible under a theoretical approach. In this respect, lines indices Fe i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 24 publications
5
36
0
Order By: Relevance
“…7. The indices that measure common spectral features with those of Fanelli et al (1992) show similar trends, with respect to T eff , log g, and [M/H], as those calculated with the Fanelli's passbands definition (Rodriguez-Merino 2004;Chavez et al 2007). Apart from the two bluest indices, the values are larger for lower gravities.…”
Section: Theoretical Indices Vs Stellar Atmospheric Parameterssupporting
confidence: 52%
See 1 more Smart Citation
“…7. The indices that measure common spectral features with those of Fanelli et al (1992) show similar trends, with respect to T eff , log g, and [M/H], as those calculated with the Fanelli's passbands definition (Rodriguez-Merino 2004;Chavez et al 2007). Apart from the two bluest indices, the values are larger for lower gravities.…”
Section: Theoretical Indices Vs Stellar Atmospheric Parameterssupporting
confidence: 52%
“…We performed this calibration, as in Chavez et al (2007), by means of a sample of stars, which were observed by GALEX and whose complete set of atmospheric parameters (T eff ,log g,[M/H]) is given in the PASTEL catalog (Soubiran et al 2010). Since the total number of these stars is not large enough to provide a good calibration, we added a sample of IUE star from the Wu et al (1983) catalog.…”
Section: Calibration Of the Theoretical Indicesmentioning
confidence: 99%
“…Some of the mid-UV indices by Fanelli et al have also been studied in theoretical Kurucz stellar spectra by Chavez et al (2007).…”
Section: Summary Of Index Behaviour With Stellar Parametersmentioning
confidence: 99%
“…The overall project consists in four main steps, namely a)-the creation of a theoretical stellar database that we have called UVBLUE 3 , b)-the comparison of such data base with observational stellar data, c)-the calculation of a set of synthetic SEDs of SSPs and their validation through a comparison with observations of a sample of Galactic globular clusters, d)-construction of models for dating local ellipticals and distant red galaxies. In Chavez (2009), we presented a summary of the results obtained in steps (a) and (b) and the reader is referred to that paper and the original references for a detailed description of the project (Rodriguez-Merino et al 2005;Chavez et al 2007). In what follows, we elaborate on the third step.…”
Section: Back In 2002 the Stellar Atmospheres And Populationsmentioning
confidence: 99%
“…As quoted by Chavez et al (2007) and Maraston et al (2009), the IUE stellar library has prevailed as the most complete for the analyses of Cimatti et al (2008). Different colors stand for five different metallicities, as described in the figure label.…”
Section: A Wish List For the World Spacementioning
confidence: 99%